ECOTOXICIDADE DO GLIFOSATO EM ABELHAS SCAPTOTRIGONA POSTICA: ESTUDO DA CONCENTRAÇÃO LETAL E SUBLETAL SOBRE BIOMARCADORES DE OXIDAÇÃO - Mikaelle de Oliveira Castilho (2023)
Herbicides represent the most used agricultural pesticides both in Brazil and around the world. Among these, glyphosate stands out as the most commercialized for weed control, with the potential to compromise the survival of bees and affect the pollination process. The accumulation of these substances in the environment and their direct contact with pollinators can result in situations of imbalance in functional homeostasis, generating oxidative stress. This study aimed to determine the median lethal concentration - LC50 and the sublethal concentration - LC10 due to ingestion of the herbicide glyphosate, in 48-hour tests, for Scaptotrigona postica bees, in addition to measuring the activity of two antioxidant enzymes: superoxide dismutase (SOD) and catalase (CAT) in individuals exposed to the determined concentrations, at 48h and 120h. In the first stage of the experiment, in order to determine the lethal and sublethal concentrations, adult bees were collected from five colonies located in the UFMS meliponary (Campo Grande, MS, Brazil). Thirty specimens were used for each exposure with their respective control group. The established concentrations were supplied to the groups diluted in sucrose syrup for a period of 48h, in doses of 0.5; 1.0; 2.0; 4.0; 8.0 and 16 µg a.i./µL diet. To calculate LC50 and LC10, mortality was counted and the data was subjected to Probit analysis, using the LdP Line® software. In the second stage of the study, fifty bee specimens, with their respective control group, were exposed to doses LC50 for 48 h and LC10 for 120 h. Macerates from the abdomen, head, wings and limbs were used to measure antioxidant enzymes. The ANOVA test was used to compare the variables between the control and treatment groups, considering the results related to enzymatic activity. The 48-hour LC50 for S. postica was 7.41 µg a.i./µL and the LC10 was 0.70 µg a.i./µL. SOD and CAT activity in bees did not differ statistically in relation to the control group at the established times and doses. The data from this study show that the LC50 of glyphosate for S. postica is within the concentration recommended in the leaflet for spraying on crops, highlighting the importance of evaluating the toxicity of this herbicide on native bees. Furthermore, it is inferred that the enzymes SOD and catalase were not good markers for oxidative stress in this species. Keywords: native bees, glyphosate, lethal concentration 50.